METACOGNITIVE AWARENESS PESERTA DIDIK MADRASAH TSANAWIYAH SE-KOTA GORONTALO PADA PENERAPAN PEMBELAJARAN DARING - Siti Asiah Tjabolo; Putriani L. Maliki; Ikal Lasido (LP2M IAIN Sultan Amai Gorontalo, 2022)
This study aims to determine the Metacognitive Awareness profile of Madrasah Students throughout Gorontalo City in the Application of Online Learning. The research method used is quantitative descriptive research, with the survey method, which is the main data collection technique by providing questions/statements that will be filled in/answered by research respondents. So the survey method is a method to obtain data/information from individuals/groups that represent a population in a representative manner. The results of the study, namely the Metacognitive Awareness Profile, consist of two main indicators, namely cognition knowledge consisting of declarative knowledge, procedural knowledge, and conditional knowledge, cognition experience/regulation indicators consisting of planning, monitoring, information management strategies, prediction strategies, and evaluation. For this reason, the indicator was used to obtain 52 questionnaire items from MAI. The research was conducted in 9 madrasahs throughout the city of Gorontalo. The data found that madrasah students throughout the city of Gorontalo in general have Metacognitive Awareness of online learning in the good and very good categories.